PENERAPAN PELAYANAN TERPADU SATU PINTU (PTSP) DALAM RANGKA PENINGKATAN INDEKS KEPUASAN MASYARAKAT PADA PENGADILAN NEGERI/ HUBUNGAN INDUSTRIAL/TINDAK PIDANA KORUPSI BENGKULU KELAS IA - Mudriyanti Mudriyanti; Muhartini Salim; Sularsih Anggarawati (UNIB Press, 2021)
The purpose of the study was to determine and analyze the application of one-stop integrated services in order to increase the community satisfaction index at the District Court/Industrial Relations/Corruption Crimes Bengkulu Class IA. The research approach is a quantitative descriptive approach supported by highly structured interviews. Collecting data using questionnaires and interviews. Data analysis used descriptive statistical analysis with frequency distribution approach and mean. Furthermore, the analysis method from the results of the interview uses the stages of Marshall and Rossman, namely reduction, classification and data presentation. The results of the study found that the implementation of PTSP services was included in a good assessment. Of the 9 service elements studied, the cost element gets the highest rating and the implementer behavior element gets the lowest rating. For the Bengkulu District Court, it is expected to be able to make SOPs that regulate the behavior of implementers in providing services, then carry out periodic evaluations or monitoring through CCTV cameras on the behavior of implementers in providing services.